Achieving high room-temperature thermoelectric performance in cubic AgCuTe. Issue 9 (4th February 2020) - Jiang, Jing; Zhu, Hangtian; Niu, Yi; Zhu, Qing; Song, Shaowei; Zhou, Ting; Wang, Chao; Ren, Zhifeng
Abstract : Average ZT of near unity provides a competitive thermoelectric conversion efficiency of ∼12% at low temperature difference of 400 K. Abstract : Although there has been significant progress in developing high-temperature thermoelectric materials, seeking promising near-room-temperature candidates has been extremely difficult, and the discovery of such materials, which would be beneficial for low-grade waste-heat power generation and cooling near room temperature, has been rarely reported. Here we report the enhanced near-room-temperature performance ( ZT max = ∼1.1 at 350 K, ZT avg = ∼1.0 between 300 K and 673 K) of copper chalcogenide (AgCu)0.995 Te0.9 Se0.1 by successfully stabilizing the face-centered cubic (FCC) phase at room temperature. Surprisingly low lattice thermal conductivity (∼0.4 W m −1 K −1 ) and a good power factor (∼13.8 μW cm −1 K −2 ) are simultaneously achieved near room temperature due to the unique properties of the FCC phase. A competitive conversion efficiency of 11% is obtained in a (AgCu)0.995 Te0.9 Se0.1 -based single leg at a low temperature difference of 400 K. The high thermal stability and low operating temperature, combined with the economically competitive efficiency, will greatly promote the application of (AgCu)0.995 Te0.9 Se0.1 -based devices in power generation from low- and medium-grade waste heat. The results also indicate a new strategy to improve the near-room-temperature performance and stability of copper chalcogenide thermoelectric materials and a new direction for further research.